Efektivitas Penerapan Hukum dalam Penanggulangan Sampah Sembarangan di Kota Medan: Sebuah Studi Literatur - Jessica Banjarnahor; Septi Maria Gultom; Lourensia Bravini Lahera; Michelle Belinda S; Ribka Nainggolan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The issue of littering in Medan City has become a significant problem, with approximately 60% of the daily waste generated remaining unmanaged. This study aims to evaluate the effectiveness of law enforcement in addressing littering in Medan City based on existing literature. One key regulation implemented is the Regional Regulation (Perda) of Medan City No. 6 of 2015, which prohibits littering and imposes penalties of up to IDR 10 million in fines or up to three months of imprisonment for violators. However, the violation rate remains high, with over 1,000 cases reported in 2023. This study finds that while regulations have been established, their effectiveness is hindered by low public awareness, weak law enforcement, and inadequate waste management infrastructure. The implications of this research indicate that law enforcement must be integrated with other strategies, such as continuous education, enhanced community participation, and the development of better waste management infrastructure. Innovation-based approaches, such as circular economy practices, can also serve as solutions to bridge the gap between regulations and actual practices. Through synergy between the government, the public, and the private sector, a more effective and sustainable waste management system can be achieved. This study is expected to contribute to the development of more holistic policies aimed at creating a cleaner and healthier environment in Medan City.